The association between family structure and adolescent smoking among multicultural students in Hawaii - Yajun Du; Paula H. Palmer; Kari-Lyn Sakuma; Jerome Blake; C. Anderson Johnson (Preventive Medicine Reports, 2015)
Objective: The purpose of this study was to examine whether the prevalence of smoking was associated with family structure among multicultural adolescents and whether there was gender disparity on the association. Methods: Data were collected from a sample of 7th graders in Hawaii who completed in-class questionnaires in 2004. The final sample included 821 multicultural students from different family structures. Descriptive analyses, Chi-square tests and logistic regression were performed to examine the prevalence of smoking and the association between family structure and smoking prevalence. Results: This sample contained students who lived in intact (61.7%), single-parent (16.5%), step-parent (15.6%), and no-parent (6.2%) families. The overall prevalence of ever/lifetime smoking was 24.0%, and was not significantly different between genders in each family structure (P > 0.05). Compared with living in intact families, living in single-parent, step-parent, or no-parent families was significantly associated with higher odds of ever/lifetime smoking among all students (P < 0.05) and living in single-parent and step-parent families was significantly associated with higher odds of ever/lifetime smoking among females (P < 0.05) and among males (P < 0.05) respectively, after adjusting for covariates. Conclusions: These findings suggest that family structure is a risk factor for smoking among multicultural students. Anti-smoking programs should consider this factor.